(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Music is considered to have a mutual relation with education and knowledge. Music is an art and is also placed high up among the world’s greatest Arts. Spiritual development and providing the pure joy to a human is the main purpose and Aim of an Art. It makes our heart and minds satisfied. We will get enthusiasm, motivation and peace. Music is considered a supreme position among all arts and fine arts. For this reason Music has proved to be extremely useful in physical and spiritual development of human being.Over the period of around ten years, global issues relating to the degradation of essential resources and pollution have increased dramatically. Shortage of fresh water, global level deforestation and land reduction are the major issues of these days. Water and air pollutions touched the peak level, which cause severe diseases a bad impact on the surrounding also.